1995
DOI: 10.1113/jphysiol.1995.sp020975
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on membrane potential and input resistance in rat hypothalamic neurones.

Abstract: 1. Whole-cell recordings were conducted in rat hypothalamic tissue slices to test the hypothesis that thermal changes in membrane potential contribute to neuronal thermosensitivity. Intracellular recordings of membrane potential and input resistance were made in eighty-two neurones, including twenty-four silent neurones and fifty-eight spontaneously firing neurones (22 warm-sensitive neurones and 36 temperature-insensitive neurones). Fifty-seven of the neurones were recorded in the preoptic and anterior hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 17 publications
11
68
1
Order By: Relevance
“…Reduced input resistance at elevated temperature is a consistent finding in a variety of neuronal types (Cao and Oertel 2005;Griffin and Boulant 1995;Klee et al 1974;Lee et al 2005;Thompson et al 1985;Volgushev et al 2000). This is also the case for SDH neurons in general (Table 1); however, when neurons were separated by discharge category the reduction in input resistance was not uniform.…”
Section: Membrane Propertiessupporting
confidence: 65%
See 2 more Smart Citations
“…Reduced input resistance at elevated temperature is a consistent finding in a variety of neuronal types (Cao and Oertel 2005;Griffin and Boulant 1995;Klee et al 1974;Lee et al 2005;Thompson et al 1985;Volgushev et al 2000). This is also the case for SDH neurons in general (Table 1); however, when neurons were separated by discharge category the reduction in input resistance was not uniform.…”
Section: Membrane Propertiessupporting
confidence: 65%
“…Extrapolating in vivo functions from data collected at room temperature has proved problematic not only for neuronal excitability (Cao and Oertel 2005;Griffin and Boulant 1995;Lee et al 2005;Thomson et al 1989;Volgushev et al 2000), but also for processes underlying synaptic transmission (Micheva and Smith 2005;Thomson et al 1989;Volgushev et al 2000). Our findings therefore provide a basis for comparing room-temperature recordings with those made at elevated temperature or in vivo.…”
Section: Comparison Of In Vitro and In Vivo Ap Dischargementioning
confidence: 92%
See 1 more Smart Citation
“…But even if there were a central cold sensor for such unusual situations, it probably would not be a TRP channel, as electrophysiological effects of temperature on hypothalamic neurons seem incompatible with mediation by TRP channels (Boulant, 2006). Indeed, several studies have found no difference between temperature-sensitive and insensitive neurons in terms of temperature's effect on resting membrane potentials and currents (Griffin and Boulant, 1995;Zhao and Boulant, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported temperature-dependent increases in input resistance [24,25]. The underlying mechanisms of thermal-induced changes in resistance are not very clear, but one intriguing suggestion that still awaits demonstration points at the alteration of membrane structure by temperature [25].…”
Section: Discussionmentioning
confidence: 99%